Regulation of pancreatic stellate cell activation by Notch3 - Haiyan Song; Yuxiang Zhang (BMC Cancer, 2018)
Abstract Background Activated pancreatic stellate cells (PaSCs) are the key cellular source of cancer-associated fibroblasts in the pancreatic stroma of patients with pancreatic ductal adenocarcinoma (PDAC), however, the activation mechanism of PaSCs is not yet known. The Notch signaling pathway, components of which are expressed in stromal cells, is involved in the fibrosis of several organs, including the lung and liver. In the current study, we investigated whether Notch signal transduction is involved in PaSC activation in PDAC. Methods The expression of Notch signaling pathway components in human PDAC was examined via immunohistochemical staining and assessed in mouse PaSCs using RT-qPCR and western blotting. Notch3 expression in both PDAC stromal cells and activated mouse PaSCs was evaluated using immunofluorescence, RT-qPCR and western blotting. The impact of siRNA-mediated Notch3 knockdown on PaSC activation was detected with RT-qPCR and western blotting, and the impact on PaSC proliferation and migration was detected using CCK-8 assays and scratch experiments. The effect of conditioned medium from PaSCs activated with Notch3 siRNA on pancreatic cancer (LTPA) cells was also detected with CCK-8 assays and scratch experiments. The data were analyzed for statistical significance using Student’s t-test. Results Notch3 was overexpressed in both human PDAC stromal cells and activated mouse PaSCs, and Notch3 knockdown with Notch3 siRNA decreased the proliferation and migration of mouse PaSCs. The levels of markers related to PaSC activation, such as α-smooth muscle actin (α-SMA), collagen I and fibronectin, decreased in response to Notch3 knockdown, indicating that Notch3 plays an important role in PaSC activation. Furthermore, we confirmed that inhibition of PaSC activation via Notch3 siRNA reduced the proliferation and migration of PaSC-induced mouse pancreatic cancer (LTPA) cells. Conclusions Notch3 inhibition in PaSCs can inhibit the activation, proliferation and migration of PaSCs and reduce the PaSC-induced pro-tumorigenic effect. Therefore, Notch3 silencing in PaSCs is a potential novel therapeutic option for patients with PDAC.